Investigation of Consistency Between the Students' Scores Using Bayesian Intraclass Correlation Coefficient in Postgraduate Students of Kerman University of Medical Sciences in 2013 - 2015 - Fatemeh Mohtasham; Yunes Jahani; Abbas Behrampour; Fariba Sharififar; Abbas Aghaei Afshar (Kerman University of Medical Sciences, 2019)
Background Evaluation of students' scores helps us indirectly examine the status of education system in university departments. Objectives In this study, in order to assess the education system, consistency between the students' scores was evaluated by measuring the Bayesian intraclass correlation coefficient (ICC) in postgraduate students of School of Public Health, Kerman University of Medical Sciences during 2013 - 2015. Methods This cross sectional study was conducted on all postgraduate students of the School of Public Health of Kerman University of Medical Sciences during 2013 - 2015. The students' scores were collected from the Office of Postgraduate Studies. First, the Bayesian ICC of students' scores was calculated for all fields. Next, cluster analysis was performed on Master's fields of study, and the Bayesian ICC was recalculated for each cluster. Data were analyzed using R 3.3.2 and OpenBUGS 3.2.3. Results Out of 117 postgraduate students, 102 (87.2%) were MSc students, and 15 (12.8%) were PhD students. The highest ICC was attributed to health education (ICC = 0.345) and the lowest to environmental health engineering (ICC = 0.023). Clustering was effective in most fields, and ICC of the clusters increased. Conclusions According to the results, consistency between the students' scores was low in the majority of fields; therefore, it is necessary to modify and improve teaching and evaluation methods.